Smart Magnetic Nanosensors Synthesized through Layer-by-Layer Deposition of Molecular Beacons for Noninvasive and Longitudinal Monitoring of Cellular mRNA - Xu, Zhichuan Jason (2017)
Non-invasive and longitudinal monitoring of gene expression in living cells is essential for understanding and monitoring cellular activities. Herein, a smart magnetic nanosensor is constructed for the real-time, noninvasive, and longitudinal monitoring of cellular mRNA expression through the layer-by-layer deposition of molecular beacons (MBs) and polyethylenimine on the iron oxide nanoparticles. The loading of MBs, responsible for the signal intensity and the tracking time, was easily tuned with the number of layers incorporated. The idea was first demonstrated with the magnetic nanosensors for glyceraldehyde-3-phosphate dehydrogenase (GAPDH) mRNA, which was efficiently internalized into the cells under the influence of magnetic field. This nanosensor allowed the continuous monitoring of the cellular GAPDH mRNA expression for 1 month. Then this platform was further utilized to incorporate two kinds of MBs for alkaline phosphatase (ALP) and GAPDH mRNAs, respectively. The multifunctional nanosensors permitted the simultaneous monitoring of the reference gene (GAPDH mRNA) and the early osteogenic differentiation marker (ALP mRNA) expression. When the fluorescence signal ratio between ALP mRNA MBs and GAPDH mRNA MBs was taken, the dynamic osteogenic differentiation process of MSCs was accurately monitored.